2003
DOI: 10.1021/ja036297t
|View full text |Cite
|
Sign up to set email alerts
|

Visual Detection of Cysteine and Homocysteine

Abstract: The determination of cysteine and homocysteine levels is of great current interest for the monitoring of desease states. A new colorimetric method for the simultaneous detection of l-cysteine and l-homocysteine has been developed. A fluorescein derivative reacts with the above amino acids, producing their respective thiazolidines resulting in color changes. Interference from other amino acids and proteins is minimal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
230
1
7

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 504 publications
(245 citation statements)
references
References 16 publications
4
230
1
7
Order By: Relevance
“…13b Highly selective probes for Hcy and Cys are being developed in our lab as potentially useful new detection agents. 22 The selective colorimetric and fluorimetric detection of Cys and Hcy in natural media is reported herein. New HPLC methods are also described.…”
Section: Homocysteine and Cysteine In Human Healthmentioning
confidence: 99%
“…13b Highly selective probes for Hcy and Cys are being developed in our lab as potentially useful new detection agents. 22 The selective colorimetric and fluorimetric detection of Cys and Hcy in natural media is reported herein. New HPLC methods are also described.…”
Section: Homocysteine and Cysteine In Human Healthmentioning
confidence: 99%
“…In recent decades, many studies have demonstrated that metabolic disorder of biothiols will lead to extreme damage in human and numerous other animals (Townsend et al, 2003;Reddie and Carroll, 2008;Weerapana et al, 2010). Specifically, a low level of biothiols in vivo may cause slowed growth, liver damage, weight loss, and some other adverse influences (Wang et al, 2005;Duan et al, 2008;Yang et al, 2012), while a high level of biothiols is closely related to Parkinson's, Alzheimer's, and cardiovascular diseases (Heafield et al, 1990;Rusin et al, 2004;Lin et al, 2008;Yang et al, 2011). Thus, a lot of effort has been put into quantifying the lowmolecule-weight biothiols in serum (Ni et al, 2015;Ghasemi et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Once the quinone is formed, even at low concentrations, it may add up a nucleophilic -SH compound relatively easily. Rusin et al 34 showed that when cysteine or homocysteine reacts with the carbonyl moieties of xanthene dyes, absorptiometric or fluorometric maxima are red-shifted as a result of -SH addition reactions, arising from intramolecular charge transfer (ICT) between electron-rich and electrondeficient groups 35 within the adduct molecule. In the case when phenols are oxidized faster than thiols, the Michael addition of nucleophilic thiols to quinones (i.e.…”
Section: Resultsmentioning
confidence: 99%